2015
DOI: 10.1007/s11270-015-2534-z
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Emerging Contaminants by Fenton and UV-Driven Advanced Oxidation Processes

Abstract: The removal efficiencies of four different parabens (methylparaben (MP), ethylparaben (EP), propylparaben (PP), and butylparaben (BP)) using Fenton reagent, UV irradiation, UV/H 2 O 2 , and UV/ H 2 O 2 /Fe 2+ were evaluated to assess the level of paraben degradation achieved using different advanced oxidation processes (AOPs). UV irradiation by itself provided paraben conversions between 27 and 38 % after a reaction time of 180 min. The UV/ H 2 O 2 system increased the paraben conversion to values between 62 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…It can be concluded from Figure 4 that pH values increase (up to 7.01) during biological d-COD degradation. This is consistent with the observations of Moreira et al [37] and Lucas et al [62], the latter stating that "this happens due to the adaptation and type of microorganisms naturally occurring along time, which clearly prefer higher pH values". According to Litaor et al [63] a decrease in dissolved organic compounds is accompanied by an increase of dissolved inorganic carbon (during the oxidation of organic matter, CO 2 is released) that result in an increase of pH to more alkaline values.…”
Section: Appl Sci 2020 10 X For Peer Review 8 Of 14supporting
confidence: 92%
“…It can be concluded from Figure 4 that pH values increase (up to 7.01) during biological d-COD degradation. This is consistent with the observations of Moreira et al [37] and Lucas et al [62], the latter stating that "this happens due to the adaptation and type of microorganisms naturally occurring along time, which clearly prefer higher pH values". According to Litaor et al [63] a decrease in dissolved organic compounds is accompanied by an increase of dissolved inorganic carbon (during the oxidation of organic matter, CO 2 is released) that result in an increase of pH to more alkaline values.…”
Section: Appl Sci 2020 10 X For Peer Review 8 Of 14supporting
confidence: 92%
“…Fenton reactions are widely used in advanced oxidation processes to decompose hydrocarbons, 65 natural organic matter, 119 and emerging contaminants. 120 In the Fenton reaction, hydroxyl radicals (OH • ) are generated via reaction between ferrous iron and hydrogen peroxide. [62][63][64]121 The hydroxyl radicals generated via the Fenton reaction can degrade more than 90% of PAM with initial MW of 5.2 × 10 6 Da at a concentration of 5000 mg/L.…”
Section: Fig 3 Hydrolysis Of Pam Generating a Carboxylic Acid Group mentioning
confidence: 99%
“…To date, only two studies have reported the electrochemical degradation of MeP in sulfate medium, focusing on its conversion to various by-products in EO with BDD at very low j [47,48]. Previous research also assessed the treatment of MeP by conventional Fenton and UV-driven AOPs [49]. However, Fenton process was inefficient for MeP degradation, whereas UV-based methods like photo-Fenton yielded better but still partial conversion values.…”
Section: Introductionmentioning
confidence: 99%